Dentin isotopic reconstruction of individual life histories reveals millet consumption during weaning and childhood at the Late Neolithic (4500 bp) Gaoshan site in southwestern China. (6th June 2018) - Yi, Bing; Liu, Xiangyu; Yuan, Haibing; Zhou, Zhiqing; Chen, Jian; Wang, Tingting; Wang, Yajuan; Hu, Yaowu; Fuller, Benjamin T.
Abstract: Here, we present results of a pilot project that measured δ 13 C and δ 15 N values in bone collagen (ribs and femora) as well as dentin serial sections to examine individual dietary life histories at a Late Neolithic (4500bp ) site known as Gaoshan Ancient City (高山古城) located on the Chengdu Plain in Sichuan Province, China. The isotopic data of the bones indicate that humans consumed C3 ‐based foods, which corresponds to the dominance of rice agriculture in this region. However, the isotopic data of the dentin serial sections of five individuals display much more positive δ 13 C values than those of the bones, strongly suggesting that millets (a C4 crop) contributed substantially to human diets during the weaning process and early childhood. Furthermore, the isotopic profiles of dentin sections of the first molars and canines demonstrate that the cession of weaning was individually variable and completed between ~2.5 and 4 years of age. Although limited in scope, this pilot study offers new evidence of millet consumption during human growth and development even though individuals relied on rice exclusively as adults. Moreover, our study provides another perspective with which to rethink the role that millets played during the development and spread of millet agriculture to the south of China in terms of cultural exchange and migration.